PENGARUH EKONOMI KREATIF DAN PROMOSI DIGITAL TERHADAP MINAT MENONTON ULANG KESENIAN JARANAN ROGO SAMBOYO PUTRO PADA GENERASI Z DI KEDIRI 2 - Ogi Permana; Nuruni Ika (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to analyze the influence of Creative Economy and Digital Promotion on Repeat Watching Interest in the Jaranan Rogo Samboyo Putro (RSP) traditional performance among Generation Z in Kediri. This study employed a quantitative approach using a purposive sampling technique on 100 Generation Z respondents who had watched an RSP performance at least once. Data were collected through questionnaires distributed at the performance location and analyzed using Structural Equation Modeling based on Partial Least Square (PLS-SEM) with SmartPLS 4.0 software. The results show that Creative Economy has a positive and significant effect on Repeat Watching Interest (path coefficient = 0.384; t = 5.030; p = 0.000), and Digital Promotion also has a positive and significant effect (path coefficient = 0.431; t = 5.377; p = 0.000), together explaining 54.1% of the variance in Repeat Watching Interest.